2020
DOI: 10.3390/met10010078
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Structure of FeOx-CaO-SiO2-MgO and FeOx-CaO-SiO2-MgO-Cu2O-PdO Slags Relevant to Urban Ores Processing through Cu Smelting

Abstract: Ferrous-calcium-silicate (commonly known as FCS) slags are used in the valuable metal recycling from urban ores through both primary and secondary copper smelting processes. In the present study, the structure of selected FCS-MgO (FCSM) and FCS-MgO-Cu2O-PdO (FCSM-Cu2O-PdO) slags, relevant to the processes, were investigated using Fourier-transform infrared (FTIR) spectrometry. Deconvolution of the FTIR spectra was carried out to calculate the relative abundance of different silicate structural units (Qn), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…According to Virgo et al [ 56 ], different anionic structural units could be identified according to the number of NBO. A superscript number is assigned to the number of bridging oxygens (BO) present in silicate tetrahedral units, with Q0 representing zero BO and all NBO ([SiO 4 ] 4− ), Q1 one BO and 3 NBO ([Si 2 O 7 ] 6− ), Q2 two BO and two NBO ([SiO 3 ] 2− ), Q3 three BO and one NBO ([Si 2 O 5 ] 2− ) and Q4 four BO and zero NBO (SiO 2 ) [ 38 , 57 , 58 ]. The addition of acidic oxides, as network formers, results in an increase in the number of BO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Virgo et al [ 56 ], different anionic structural units could be identified according to the number of NBO. A superscript number is assigned to the number of bridging oxygens (BO) present in silicate tetrahedral units, with Q0 representing zero BO and all NBO ([SiO 4 ] 4− ), Q1 one BO and 3 NBO ([Si 2 O 7 ] 6− ), Q2 two BO and two NBO ([SiO 3 ] 2− ), Q3 three BO and one NBO ([Si 2 O 5 ] 2− ) and Q4 four BO and zero NBO (SiO 2 ) [ 38 , 57 , 58 ]. The addition of acidic oxides, as network formers, results in an increase in the number of BO.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of acidic oxides, as network formers, results in an increase in the number of BO. On the other hand, basic oxides act by disrupting the network, thus producing free oxygen ions (O 2− ) and NBO (O − ) and reducing the number of BO (O 0 ) [ 58 ], according to the Equation (1): O 0 + O 2− = 2O − …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hasan et al [18] studied the structure of ferrous calcium-silicate slags with MgO addition using Fouriertransform infrared (FTIR) spectrometry. They showed that the overall degree of polymerization (DOP) of the silicate network and the average number of bridging oxygen (BO) decreased with increasing both the Fe/SiO 2 ratio and basicity (defined as CaO/SiO 2 ratio).…”
Section: Introductionmentioning
confidence: 99%